BCG vaccination-induced long-lasting control of Mycobacterium tuberculosis correlates with the accumulation of a novel population of CD4+IL-17+TNF+IL-2+ T cells. Issue 1 (1st January 2015) - Cruz, Andrea; Torrado, Egídio; Carmona, Jenny; Fraga, Alexandra G.; Costa, Patrício; Rodrigues, Fernando; Appelberg, Rui; Correia-Neves, Margarida; Cooper, Andrea M.; Saraiva, Margarida; Pedrosa, Jorge; Castro, António G.
Highlights Mice were vaccinated with BCG for 21 or 120 days before challenged with Mtb. Mice challenged 120 days after BCG vaccination displayed improved control of Mtb. BCG-mediated control of Mtb correlates with the IL-17 response and is independent of the magnitude of the IFN-γ response in the lung. Long-lasting control of Mtb correlates with the accumulation of CD4+ T cells producing IL-17, TNF and IL-2.